Is personality reflected in the gestures of second language speakers? - Lopez-Ozieblo, Renia (Frontiers in Psychology, 2024)
Previous studies on gestures and personality suggest an ambiguous picture of the effects of the various personality dimensions on the different types of speech-gestures and adaptors. In foreign language learning an additional variable to take into account is proficiency, which some studies have shown to affect gestures. In this study, we explore how various intrinsic variables, including personality, proficiency, gender and age affect the gestures of 61 Cantonese speakers of English as a second language.Participants were asked to narrate a video cartoon. Their proficiency and the frequency of gestures produced was based on those narrations. A functional categorization of gestures was followed, dividing them into semantic and discursive, and that also noted adaptors and microgestures, referred to as "flutters". Personality was self-reported using the 44 question Big-Five inventory.Correlations and a series of generalized linear models were developed to explore the interplay between variables. Agreeableness was found to be positively correlated with semantic gestures; and neuroticism and age were negatively correlated with flutter duration. Contrary to the findings from previous studies, no significant relationships were found between neuroticism and adaptors or semantic gestures, nor between extraversion or openness and semantic gestures. Proficiency and gender had little effect on gestures. As personality has been shown to be an important factor in gesture production in mother tongue speakers, we expected to also see a similar result with foreign language speakers, this not being so suggests that other variables, aside from those tested, should be considered. In particular, the results suggest that emotion and emotional constructs, such as anxiety, self-confidence or empathy, might have a greater impact on gesture production than proficiency or personality, a point which should be taken into account especially in language evaluation contexts or professional contexts with second language speakers.